2004
DOI: 10.1007/s00436-003-1008-1
|View full text |Cite
|
Sign up to set email alerts
|

A cysteine protease from Taenia solium metacestodes induce apoptosis in human CD4+ T-cells

Abstract: Here we investigated whether the depletion of CD4+ lymphocytes, observed in mononuclear cells incubated with Taenia solium metacestode E/S products or with living cysts was due to apoptosis. Using the deoxynucleotidyl transferase-mediated dUTP nick-end labelling (TUNEL), electron microscopy and DNA gel electrophoresis, we found signs of apoptosis in these cells. Results showed that cysteine protease activity was responsible for this effect, since E-64 prevented cell death in all cases. Electron microscopy stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 38 publications
2
22
0
1
Order By: Relevance
“…The depletion of T cells, particularly the CD4 + population Molinari et al 1987), and the suppression of T-cell proliferative responses (Molinari et al 1993a), have been described in cysticercotic pigs. The present results suggest that implanted metacestodes release the suppressive MF in vivo, which may be responsible, along with other molecules such as paramyosin (Laclette et al 1992) and cysteine proteases (White et al 1992;Molinari et al 2000;Tato et al 2004), for suppressing the host immune system. As far as we are aware, the down-modulation induced by F1 is not caused by the stimulation of a particular subset of cells (Th1 or Th2 for instance), but is due to the interaction of this molecule with different cells inducing the inhibition of cytokine production in a non-specific manner.…”
Section: Discussionmentioning
confidence: 84%
“…The depletion of T cells, particularly the CD4 + population Molinari et al 1987), and the suppression of T-cell proliferative responses (Molinari et al 1993a), have been described in cysticercotic pigs. The present results suggest that implanted metacestodes release the suppressive MF in vivo, which may be responsible, along with other molecules such as paramyosin (Laclette et al 1992) and cysteine proteases (White et al 1992;Molinari et al 2000;Tato et al 2004), for suppressing the host immune system. As far as we are aware, the down-modulation induced by F1 is not caused by the stimulation of a particular subset of cells (Th1 or Th2 for instance), but is due to the interaction of this molecule with different cells inducing the inhibition of cytokine production in a non-specific manner.…”
Section: Discussionmentioning
confidence: 84%
“…This hypothesis was discarded because no increased peripheral IL10 levels were detected, neither in supernatant of speciWcally stimulated cells nor in plasma from inXammatory and non-inXammatory NC patients (data not shown). Taking into account the possible existence of suppressive parasite excretion/secretion factors [37][38][39], their presence in sera and CSF was evaluated. As shown in this study, no evidences of suppressive factors were found.…”
Section: Discussionmentioning
confidence: 99%
“…*p<0.05, **p<0.02 sylation of cysteine-containing proteins (e.g., cysteine proteases) appears to be a common and widespread mechanism, thus parasitic cysteine proteases can be NO targets (Rivero 2006). Recently, it has been demonstrated that T. crassiceps and T. solium metacestodes release cysteine proteases at the host-parasite interface that appear to play a role in favoring parasite survival by breaking IgG and by inducing apoptosis of CD4 + cells (Tato et al 2004;Baig et al 2005). NO may therefore be an important inhibitor of the immunomodulatory cysteine protease activities in cysticercosis.…”
Section: Discussionmentioning
confidence: 99%